Masculinity, race and national identity: representations of non-Japanese men’s speech in contemporary Japanese novels - Suzuki, Satoko (Gender and Language, 2020)
Language ideologies have been of central concern to the study of Japanese language, gender and society. Many scholars have researched ideologies surrounding representations of Japanese women’s speech; however, investigations of representations of men’s speech have been limited. This study contributes to filling this gap through the analysis of non-Japanese male characters found in contemporary Japanese novels. The article reveals that authors assign strongly masculine expressions to their East Asian characters much more frequently than to their white characters and argues that these differentiated representations of non-Japanese male characters’ speech reproduce and are influenced by ideologies concerning cultural nationalism, racial determinism, class and sexuality. Linguistic data are presented that both unsettle the constructed image of Asian males as asexual beings and question the historically assumed relationship between gendered language and authenticity.
Keywords: arts; asie; cours; discipline; histoire et politique; japon; lin2685; linguistique; masculinité; premier cycle; représentation des hommes; régions géographiques; sciences humaines; sofia; thématiques; études littéraires

Still a superwoman? How female academics from the former Soviet Union negotiate work-family balance abroad - Antoshchuk, Irina A; Gevinner, Irina (Monitoring Obshchestvennogo Mneniya: Ekonomicheskie i Sotsial'nye Peremeny, 2020)
Since the 1930s, a peculiar 'working mother' gender contract was dominant in the Soviet Union formally empowering women. The pressing expectation of this contract and a necessity to combine motherhood, housework and employment led to the image of the near superwoman who 'has it all'. This paper examines whether highly-skilled Russian-speaking female academics continue to adhere to this cultural ideal striving for work-life balance after migration to the UK and Germany. Based on qualitative interviews with 22 female scholars, the article provides a typology of scenarios for negotiating professional and private life. It elaborates on how role-related partners contribute to achieving balance between paid employment and mothering and explores the consequences for women's well-being. Moreover, the study suggests a feminist approach to analyzing work-family balance, which valorises women's point of view, emphasizing motherhood, children and family relations as an essential personal and social value, while also documenting the increasing challenges faced in the realization of these life priorities. © 2020 Russian Public Opinion Research Center, VCIOM. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; allemagne; asie; charge mentale; conciliation famille-travail; discipline; europe; ex-URSS; famille; femmes* russophones; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; russie; régions géographiques; sciences humaines; sociologie; thématiques; travail